Sytuacja prawna pracowników powyżej pięćdziesiątego roku życia - Dębska, Monika Magdalena; Dębski, Maciej (Prawo Kanoniczne, 2011)
Non-discrimination of treatment – also on the grounds of age – is a fundamental rule of Polish labour legislation. That rule is expressed in art. 32(2) of the Polish Constitution, art. 1 of Directive 2000/78/EC and art. 113 of the Polish Labour Code. According to art. 6 of Directive 2000/78/EC, art. 183b § 2 of the Polish Labour Code and ECJ case law, exceptions from that rule are permissible if they are justified by a legitimate aim and if the means of achieving that aim are appropriate and necessary. These exceptions include the legitimacy of termination of employment relationships with workers for the sole reason of their reaching the age of retirement. Indeed, such termination can be justified by employment policy. On the other hand, by virtue of art. 39 of the Labour Code, during four years prior to reaching retirement age workers benefit from the so-called protection period, which – with some exceptions – prohibits termination of their employment contracts or work and pay agreements. On October 17th, 2008, the Polish government adopted a program named Solidarity of generations – action for Increasing Occupational activity of Persons aged 50+, within which professional development training and apprenticeship programs were opened to people aged 50 and over, and legislation was introduced to promote their employment.